Explaining the Paradox in Gender Differential in Health. - Dhak, Biplab (2010)
The present paper seeks to provide certain explanations in the Indian context for the recently observed paradox of gender differential in health. There has been a mismatch between gender differential in mortality and morbidity: females experiencing a low rate of mortality despite being confronted with a high level of morbidity compared to males, particularly from the age of 30 years. Using multiple data sets, it has been observed that gender differential in diseases patterns, severity in illness and greater risk behaviour among males play an important role in explaining the paradox.